Strategi Komunikasi Pemasaran Digital Rabando Group Dalam Meningkatkan Brand Awareness di Instagram - Robiyah, Nurul; Soraya, Iin; Pratiwi, Cindya Yunita (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The development of information technology has changed the pattern of marketing communication from conventional to digital methods, allowing companies to reach a wider audience with higher efficiency. Rabando Group, as a company engaged in online distribution, realizes the importance of utilizing social media, especially Instagram, as a strategic platform to increase brand awareness. The purpose of this study is to determine Rabando Group's digital marketing communication strategy in increasing brand awareness on Instagram. The data collection method in compiling the thesis uses observation, interview, documentation and literature study methods with the analysis method in the form of qualitative analysis, namely a data analysis method without using statistical analysis. The results of the study show that Rabando Group utilizes the AIDA strategy to increase brand awareness on Instagram. At the Attention stage, the brand attracts the audience's attention with attractive visual content and consistent uploads, making the brand